2014
DOI: 10.1093/icvts/ivt551
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and safety of thoracic paravertebral and epidural analgesia for thoracic surgery: a systematic review and meta-analysis

Abstract: Though once considered the gold standard, epidural anaesthesia has complications that may be significant and include hypotension, urinary retention, partial or patchy block and, in rare cases, devastating neurological injuries also. Paravertebral block (PVB) is an alternative technique for unilateral surgical procedures like thoracotomy, which may offer similar analgesic effectiveness and a more favourable side-effect profile than epidural analgesia. This systematic review and meta-analysis of published random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
2
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 28 publications
5
119
2
13
Order By: Relevance
“…If the values for continuous variables were reported as median and as interquartile range (IQR) or total range, the mean value was estimated using the median and the low and high ends of the range for samples smaller than 25; for samples greater than 25, the actual median was used [6]. The mean and SD were estimated from the median and the low and high ends of the range for samples smaller than 15, as range/four for samples from 15 to 70, and as range/six for samples more than 70 [6].…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…If the values for continuous variables were reported as median and as interquartile range (IQR) or total range, the mean value was estimated using the median and the low and high ends of the range for samples smaller than 25; for samples greater than 25, the actual median was used [6]. The mean and SD were estimated from the median and the low and high ends of the range for samples smaller than 15, as range/four for samples from 15 to 70, and as range/six for samples more than 70 [6].…”
Section: Data Synthesismentioning
confidence: 99%
“…The mean and SD were estimated from the median and the low and high ends of the range for samples smaller than 15, as range/four for samples from 15 to 70, and as range/six for samples more than 70 [6]. If only an IQR was available, SD was estimated as IQR/1.35 [15,24].…”
Section: Data Synthesismentioning
confidence: 99%
“…It is associated with less incidence of failed block and reduces hypotension and urinary retention when it is compared with TEA. Several recent reviews and meta-analyses defend its beneits [51][52][53], and it is a standard practice in some UK hospitals for minimally invasive esophagectomy. Local data also show shorter stays in the intensive therapy unit comparing with TEA.…”
Section: Thoracic Epidural Analgesia (Tea) Versus Paravertebral Analgmentioning
confidence: 99%
“…After reviewing studies in several meta-analyses suggesting an increased incidence of hypotension with TEA, we found that, in virtually all of these trials, the investigators used bupivacaine or ropivacaine concentrations that were higher or equal to 0.125% or 0.2%, respectively. 11,12 Unfortunately, few studies have investigated the relationship between much lower concentrations of local anesthetics (e.g., ''ultra-low-dose'' epidurals) and the incidence of lower limb motor block, hypotension, and IAFs in the surgical population. Moreover, studies consistently report a higher incidence of lower limb motor block with lumbar epidurals than with thoracic epidurals.…”
mentioning
confidence: 99%
“…Après avoir examiné les études dans plusieurs méta-analyses suggérant une augmentation de l'incidence de l'hypotension avec la TEA, nous avons constaté que dans quasiment tous ces essais, les investigateurs avaient utilisé des concentrations de bupivacaïne ou de ropivacaïne qui étaient égales ou supérieures à, respectivement, 0,125 % ou 0,2 %. 11,12 Malheureusement, peu d'études se sont intéressées aux rapports entre des concentrations d'anesthésiques locaux beaucoup plus faibles (par exemple, les péridurales à « dose ultra basse ») et l'incidence des blocs moteurs des membres inférieurs, l'hypotension et les accidents et chutes des patients hospitalisés dans la population chirurgicale. De plus, les études ont régulièrement signalé une incidence des blocs moteurs des membres inférieurs plus élevée avec les péridurales lombaires qu'avec les péridurales thoraciques.…”
unclassified